2017
DOI: 10.5658/wood.2017.45.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Species of Soft Wood Decay Resistance for Heat-Treated Wood Using the Catalyst (H2SO4)

Abstract: This study was conducted to evaluate the resistance of heat-treated wood using the catalyst to decay caused by fungi for sapwood and heartwood of two tree species, Korean red pine (Pinus densiflora) and Japanese larch (Larix kaempferi), respectively. Wood samples were immersed for 10 min in sulfuric acid (7.5%) and then heat-treated at 130℃ for 90 min. Fomitopsis palustris, a brown-rot fungus, was used to examine the decay resistance of Korean red pine and Japanese larch wood. Weight and density of wood from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…The effects of super heated steam method of heat treatment on wood properties have been explored by Park et al (2016Park et al ( , 2018. On the other hand, Won et al (2017) used sulfuric acid (7.5%) immersion as a catalyst before heat treatment at 130 °C for 90 minutes that improved the decay resistance of Korean red pine (Pinus densiflora) and Japanese larch (Larix kaempferi) woods from brown rot fungus (Fomitopsis palustris).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of super heated steam method of heat treatment on wood properties have been explored by Park et al (2016Park et al ( , 2018. On the other hand, Won et al (2017) used sulfuric acid (7.5%) immersion as a catalyst before heat treatment at 130 °C for 90 minutes that improved the decay resistance of Korean red pine (Pinus densiflora) and Japanese larch (Larix kaempferi) woods from brown rot fungus (Fomitopsis palustris).…”
Section: Introductionmentioning
confidence: 99%
“…목재의 열처리는 고온가열로 목재성분의 열분해 수준을 조절하면서 화학적 성분 변화를 유도하여 치수안정성 및 내후성 증대 등을 목표로 하는 가공방법이다 (Kim, 2016). 열처리에 의한 목재의 특성 변화에 관한 연구는 다수 보고되어 왔다 (Čermák and Dejmal, 2013;Tu et al, 2014;Park et al, 2015;Chung et al, 2016;Gong et al, 2016;Hidayat et al, 2016;Lee and Kim, 2016;Jang et al, 2017;Hidayat et al, 2016;Won et al, 2017;Park et al, 2018). 목재를 열처리하면 추출물이 제거되고, 헤미셀룰로오스가 분해되며 셀룰로오스와 리그닌의 변화가 일어나는데, 열처리에 의한 목재의 재색변화는 헤미셀룰로오스의 감소에 의한 것으로 추정된다 (Kim, 2016;Garrote et al, 1999).…”
Section: 서 론unclassified
“…Heat treatment of wood is a type of polishing method that produces dimensional stability and increases weather resistance by controlling the wood's thermal degradation and changing its chemical composition (Kim, 2016). Several studies have reported heat-induced changes in wood properties (Čermák and Dejmal, 2013;Tu et al, 2014;Park et al, 2015;Chung et al, 2016;Gong et al, 2016;Hidayat et al, 2016;Lee and Kim, 2016;Jang et al, 2017;Hidayat et al, 2016;Won et al, 2017;Park et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Wood, as a natural material, has various excellent properties and has been extensively utilized over centuries. However, wood is easily subjected to biodeterioration caused by microorganisms (Cao and Yu, 2010;Lee et al, 2017;Won et al, 2016;Won et al, 2017), which greatly limits its utilization. An effective way to provide wood with decay resistance in practice is by treating with preservative (Humar and Lesar, 2008;Kartal et al, 2015;Lee et al, 2016;Sen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%